2007
DOI: 10.6063/motricidade.3(1).684
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos niveis de ansiedade em praticantes de atletismo

Abstract: Characterization of anxiety levels among track and fi eld athletesThe purpose of this study was to characterize the levels of anxiety among young track and fi eld athletes. The sample consisted of 147 athletes (89 males and 58 females). These were divided according to the independent variables defi ned for the present study, namely: competitive agegroup, sport and ranking. The4 instruments used were the CSAI-2 and ICPC. The statistical procedures used were the descriptive and correlation techniques. In general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 4 publications
0
4
0
10
Order By: Relevance
“…Correlations between SC, CA and SA were classified as moderate and weak. According to Vasconcelos-Raposo, Lázaro, Teixeira, Mota, and Fernandes (2007), the lower the CA and SA values, the higher the SC scores. The correlations showed that men have moderate negative correlations for SA and SC, while women have shown a low correlation between SA and SC.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between SC, CA and SA were classified as moderate and weak. According to Vasconcelos-Raposo, Lázaro, Teixeira, Mota, and Fernandes (2007), the lower the CA and SA values, the higher the SC scores. The correlations showed that men have moderate negative correlations for SA and SC, while women have shown a low correlation between SA and SC.…”
Section: Discussionmentioning
confidence: 99%
“…IInstrument used to evaluate depression state. e classi cation indicates the folowing depression socres: minimal (0-9), mild (10-15), mild to moderate (16)(17)(18)(19), moderate to severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), severe (30-63) 31 . Cronbach's alpha value for this questionnaire was 0.92. should note how it feels in relation to it adjective.…”
Section: Beck Depression Inventory 30mentioning
confidence: 99%
“…On the competitive context, evolved people are constantly submited to a trully observation bombing, opinions and judments that can create unsuitable expectations, aims and pressions for an athlete development. In some cases, practioners see competition like a threat, what would be negative to their performance [17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Assim, recomenda-se a realização de pesquisas também em outros estados e contextos avaliativos, além de se investir na avaliação da influência da ansiedade no desempenho. Apesar de já existirem estudos que buscaram avaliar essa relação (Almeida, Behlau, & Leite, 2011;Hausknecht, Day & Thomas, 2004;In'nami, 2006;Oliveira & Duarte, 2004;Pereira, Barros, & Mendonça, 2012;Silva & Sponda, 2009;Vasconcelos-Raposo, Lázaro, Mota, & Fernandes, 2007), os resultados ainda são pouco expressivos.…”
Section: Considerações Finaisunclassified
“…Considerando o contexto avaliativo de forma mais ampla, há na literatura muitos estudos que analisaram a relação entre ansiedade e desempenho: em processos seletivos para conseguir um emprego, em apresentações em público, tendo como foco o desempenho relacionado a habilidades musicais e em atividades desportivas (Almeida, Behlau, & Leite, 2011;Hausknecht, Day & Thomas, 2004;In'nami, 2006;Oliveira & Duarte, 2004;Pereira, Barros, & Mendonça, 2012;Silva & Sponda, 2009& Vasconcelos-Raposo, Lázaro, Mota, & Fernandes, 2007. Entretanto, está longe de se estabelecer um consenso de que a relação entre ansiedade e desempenho é simplesmente de que uma está inversamente relacionada com a outra.…”
Section: Introductionunclassified